CHARACTERISTICS OF UNDEVELOPED PREGNANCY - Khonxujayeva M. M.; Nazirova M. U. (Modern American Journals, 2025)
For follow-up, 42 women with underdeveloped fetuses were observed, and their medical history, placental histological examinations and blood tests were studiedAmong the various forms of pregnancy termination, a special place is occupied by missed abortion, which occurs during the first trimester and is characterized by a prolonged retention of the fetus in the uterine cavity. This pathology has a separate code in the 10th edition of the International Statistical Classification of Diseases (1995). The problem of missed pregnancy is not only clinically relevant, but also socially relevant, since this pathology is very common (10-20%) in the composition of reproductive losses. The retention of a dead fetus in the uterine cavity poses a serious threat not only to the health of the woman, but also to her life.
Keywords: Antiphospholipid syndrome, missed pregnancy, colpitis, infertility, prostaglandins, misoprostol, anembryonia, polycystic ovary syndrome.